Metalik malzemelerin bilyalı dövme uygulaması sonrası tribolojik davranışının deneysel olarak incelenmesi - Balyalı, Harun Arda (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada Ti6Al4V titanyum alaşımı ve AISI 316 paslanmaz çelik malzemelerin bilyalı dövme sonrası tribolojik davranışlarının karakterize edilmesi amaçlanmıştır. Bu amaçla Ti6Al4V alaşımı ve AISI 316 paslanmaz çelik numunelere farklı Almen dövme şiddetleri (A 0.006, A 0.008 ve A 0.010) ile bilyalı dövme uygulanmıştır. Almen dövme şiddetine bağlı olarak numunelerin yüzey pürüzlülüğü, sertlik, sürtünme katsayısı ve aşınma hızı değerlerindeki değişimler incelenmiştir. Numune yüzey topografyasındaki değişimler için optik mikroskop ve taramalı elektron mikroskobu ile incelemeler yapılmıştır. Bilyalı dövme işlemine bağlı olarak numunelerin yüzey pürüzlülüğünde, sertliğinde ve tribolojik davranışlarında önemli oranda değişiklikler gözlemlenmiştir. Bilyalı dövme işlemi sonrasında numunelerin yüzey pürüzlülüğü ve sertlik değerlerinde önemli değişiklikler gözlemlenmiştir. Ti6Al4V alaşımı ve AISI 316 paslanmaz çelik malzemelerin yüzey pürüzlülüğü ve sertlik değerleri bilyalı dövme işlemi sonrasında artış göstermiştir. Ayrıca Almen dövme şiddetinin artışı ile yüzey pürüzlülüğü ve sertlik değerlerinin arttığı tespit edilmiştir. Buna ek olarak AISI 316 paslanmaz çelik numunelerin yüzey pürüzlülüğü ve sertlik değerlerindeki yüzde artış oranları, Ti6Al4V alaşımının yüzde artış oranlarından yüksek olduğu görülmüştür. Bu sonuç paslanmaz çelik numunelerin plastik şekil değiştirme kabiliyetinin daha iyi olmasının bir neticesidir. Numunelerin sürtünme katsayısındaki değişimler çalışma şartlarının kuru ve yağlı olmasına bağlı olarak incelenmiştir. Bilyalı dövme işlemi etkisiyle AISI 316 paslanmaz çelik numunelerin kuru çalışma şartlarında sürtünme katsayılarında yükselme gözlemlenmiştir. Kayma hızının artması ile sürtünme katsayısı değerlerinin yükseldiği görülmüştür. Uygulanan normal yükün artması ile sürtünme katsayısı değerlerindeki değişim farklılıklar göstermiş olup, sabit artış veya azalış gözlenmemiştir. Ti6Al4V alaşımının kuru çalışma şartlarındaki sürtünme katsayısına bilyalı dövme işleminin etkileri net olarak gözlemlenememiştir. Aynı şekilde kayma hızının artmasına bağlı olarak kuru ortamdaki Ti6Al4V alaşımının sürtünme katsayılarında değişim tespit edilmemiştir. Genel olarak uygulanan normal yükün artışı ile titanyum alaşımının sürtünme katsayısı değerlerinde azalma gözlenmiştir. Yağlayıcı bulunan çalışma şartlarındaki A0.006 ve A0.008 Almen dövme şiddetli AISI 316 paslanmaz çelik numunelerin sürtünme katsayılarında düşüş gözlemlenmiştir. Ek olarak kayma hızının artışı ile sürtünme katsayılarında azalma tespit edilmiştir. Normal kuvvetin artması ile sürtünme katsayılarında çok küçük değer artışları gözlenmesine rağmen, bu küçük değer artışlarına göre sürtünme katsayısının arttığı söylenememektedir. Ti6Al4V alaşımını yağlayıcı bulunan sınır sürtünme şartlarındaki sürtünme katsayısının A 0.006 Almen dövme şiddetli numunelerde azalma gösterirken, A 0.008 ve A 0.010 Almen dövme şiddetleriyle dövülen numunelerde yükselme göstermiştir. Kayma hızının artmasına bağlı olarak ise Ti6Al4V alaşımının yağlayıcı madde bulunan sınır sürtünme şartlarındaki sürtünme katsayısının değişkenlik gösterdiği görülmüştür. Kayma hızının artması ile dövülmemiş ve A 0.006 Almen dövme şiddeti ile dövülen numunelerin sürtünme katsayıları azalırken, A 0.008 ve A 0.010 Almen dövme şiddetli numunelerde sürtünme katsayılarında daha stabil değerler elde edilmiştir. Uygulanan normal yükün artması ile dövülmemiş ve A 0.006 Almen dövme şiddeti ile dövülen numunelerin sürtünme katsayısı değerlerinin çok küçük değerlerde azaldığı, A 0.008 ve A 0.010 Almen dövme şiddeti ile dövülen numunelerin sürtünme katsayısı değerlerinin arttığı tespit edilmiştir. Sunulan çalışmada kuru ve yağlı çalışma şartlarında Ti6Al4V alaşımı ve AISI 316 paslanmaz çelik numunelerin aşınma hızları da incelenmiştir. Paslanmaz çelik numunelerin 500 metre kayma mesafesi boyunca 10N normal yük, 1m/s kayma hızıyla kuru sürtünme şartlarındaki aşınma hızları bilyalı dövme işlemi sonrasında artış göstermiştir. Diğer yandan Titanyum alaşımının kuru sürtünme şartlarındaki aşınma hızlarında değişim gözlenememiştir. Titanyum malzemede Almen dövme şiddeti artışıyla aşınma hızları değişmezken, paslanmaz çelik numunenin kuru ortamdaki aşınma hızlarında düşüş gerçekleşmiştir. Yağlayıcı madde bulunan sınır sürtünme şartlarında numunelerin aşınma miktarları 500m, 1000m, 2000m, 3000m, 4000m ve 5000m kayma mesafesinde ölçülmüştür. 10N normal yük altında, 1m/s kayma hızında titanyum alaşımı ve paslanmaz numunelerin aşınma hızları bilyalı dövme uygulaması sonrası düşüş sergilemiştir. Ayrıca Almen dövme şiddetinin artışı ile aşınma hızlarının azaldığı görülmüştür. Bunun yanında 3000 metre kayma mesafesinden sonra aşınma miktarlarının durmaya yakın olduğu gözlemlenmiştir. Kuru ve sınır sürtünme şartlarındaki aşınma hızları karşılaştırıldığında Ti6Al4V alaşımının aşınma dayanımının her iki çalışma şartlarında da paslanmaz çelikten daha yüksek olduğu görülmüştür. 500 metre kayma mesafesinde, 10N normal yük altında ve 1m/s kayma hızında titanyum alaşımı ve paslanmaz çelik malzemelerin her iki farklı çalışma şartlarındaki aşınma hızları incelendiğinde Ti6Al4V alaşımının yağlayıcı madde bulunan sınır sürtünme şartlarında aşınma hızlarının en düşük olduğu tespit edilmiştir. Elde edilen sonuçlarda sınır sürtünme şartlarında aşınma dayanımlarının bilyalı dövme işlemi ile arttığı neticesine varılmıştır. Bilyalı dövülmüş numunelerin yüzeyleri optik mikroskop ve taramalı elektron mikroskobu ile incelenerek yüzey topografyalarındaki değişimler gözlemlenmiştir. Yüksek hızlarda ve tekrarlı bir şekilde malzeme yüzeyine çarpan çelik bilyaların etkisi ile malzemelerin yüzeylerinde plastik deformasyonlar oluşmuştur. Numunelerin yüzeylerinde oluşturulan deformasyonların sonucunda oluşan çukur ve tümsek yapılar yüzey morfolojilerinin incelenmesi çalışmalarında tespit edilmiştir. Aşınma yüzeyleri incelendiğinde Almen dövme şiddetinin değişmesi aşınma mekanizmasını değiştirmezken, aşınma şiddetinde değişikliğe yol açtığı görülmüştür. Bilyalı dövme işlemi ve işlem parametrelerinin malzeme özelliklerinin önemli derecede etkilediği, tribolojik davranışlarında etkin rol oynadığı sonucuna varılmıştır.

In this study, characterization of tribological behaviour of Ti6Al4V alloy and AISI 316 stainless steel bar materials after shot peening implementation is evaluated. It is aimed to understand the relationship between the Almen intensity and tribological behaviour of Ti6Al4V alloy and AISI 316 stainless steel. For that purpose, Ti6Al4V alloy and AISI 316 stainless steel samples were shot peened with different (A 0.006, A 0.008 and A 0.010) Almen peening intensity. Surface roughness, hardness, friction coefficient and wear rate values of samples were examined depending on the Almen peening intensity. Optical microscopy and scanning electron microscopy (SEM) examinations were performed for to examine the variations on the sample surface topography and possible wear mechanisms were discussed. It is observed that tribological behaviour of the sample was significantly varied depending on the shot peening implementation, surface roughness and hardness. In this study, not only experimental investigation of shot peening implementation was practiced but also effects of parameters of shot peening on materials are investigated. On the other hand, a comprehensive literature survey was conducted about shot peening implementation. Shot peening is a cold working process that involves the bombardment of spherical balls against the surface of components, thus it causes high plastic deformation on the surface of materials. Shot peening is an important technology of mechanical treatment of surface that modifies the surface with elastic residual stress distribution, increased surface hardness, and higher near-surface dislocation density. As an important surface treatment method, shot peening implementation is widely used in automotive and aerospace industries in order to improve surface properties. It is used for various components such as railway and automobile leaf springs, helical springs of all types, gears, axle bearings, crankshafts, pneumatic drills, milling cutters, connecting rods, coil springs, cylinder blocks, valve springs, and washers. Titanium alloys (specifically Ti6Al4V alloy) have been extensively used in aerospace and automotive applications due to their good mechanical, chemical and physical properties such as high strength to weight ratio, high toughness, low density, excellent corrosion resistance and high working temperature. Moreover, Ti6Al4V alloy is significantly stronger than commercial pure titanium while having the same stiffness and thermal properties. These superior properties make Ti6Al4V alloy usage preferable in the blades and disks of aircraft compressors, the rotor blades of helicopters, valves, piping and centrifugal pumps used in industrial waste water systems. However, they present relatively poor wear resistance due to their poor tribological properties. Stainless steels are used widely due to theirs high corrosion resistance. Especially in chemical industry, theirs variety types are developed for different and difficult operation conditions. Stainless steels have been used in food, chemical, automotive, medical, petroleum chemical industry, turbine, marine and white goods industry due to good mechanical properties, easily processability, healthy and easy cleanability properties. Moreover, it can be used in low and high temperature environment. In different operation conditions, new generation alternative materials are needed. As a result, those stainless steels are developed with using of alloy elements. However, these processes are expensive and difficult. On the other hand, studies about the surface improvement treatments of stainless steel materials continue. For that purpose, investigation of tribological behaviours of Ti6Al4V alloy and AISI 316 stainless steel is aimed after shot peening implementation. Ti6Al4V alloys and AISI 316 stainless steel materials used in this study was supplied as bar (12mm diameter). After shot peening implementations, the samples were cut as cylinder of 15 mm from these shot peened bars. In experimental stage of this present study, Surface roughness, hardness, friction coefficient and wear rate values of samples were examined depending on various parameters such as the Almen intensity, normal force, sliding speed and operation conditions. In order to investigate the effects of shot peening implementation, shot peened samples were investigated by using a non-contact laser optical profilometer (Nanovea PS50) and surface hardness of the samples were measured by using a Digital Micro-hardness Tester (Metkon Duroline M). The surface roughness values, 3-D surface morphologies and micro-hardness of the samples were obtained and examined. Three tests for each sample were carried out and then the average surface roughness for each sample was calculated. Moreover, scanning electron microscopy investigations of shot peened surfaces of Ti6Al4V alloy were conducted. The micro-hardness of the samples was measured with an experimental force of 1000gf and a loading time of 15s. Six tests for each sample were carried out and then the average micro hardness for each sample was calculated. Surface roughness and hardness of Ti6Al4V and AISI 316 stainless steel show significantly alteration with shot peening implementation. After shot peening implementation, compared to untreated sample, surface roughness and hardness values of samples increased as expected. Besides, surface roughness and hardness values of samples increased with increases in Almen intensity. Moreover, the surface roughness and the hardness of AISI 316 stainless steels increased dramatically compared to Ti6Al4V alloy. Thus, this behaviour can be explained due to the better ability of plastic deformation of the stainless steel alloy compared to Ti6Al4V alloy. Variation of the friction coefficient of the samples was investigated depending on the dry and boundary friction operation conditions. Friction coefficient of AISI 316 stainless steel increased with shot peening implementation in dry friction operation conditions. Friction coefficient of AISI 316 stainless steel increased with increases in sliding velocity. Moreover, friction coefficient of AISI 316 stainless steel changed nonuniform with increasing the normal force. It is observed that in general the coefficient of friction of Ti6Al4V alloy is not affected by shot peening in dry friction operation conditions. In addition to this, in dry friction conditions, friction coefficient of Ti6Al4V alloy don't change with increases in sliding velocity. Generally, friction coefficients of Ti6Al4V alloy decreases with increasing the normal force. The friction coefficient of AISI 316 stainless steel samples peened with A0.006 and A0.008 Almen intensity decreased in boundary friction operation conditions. Furthermore, the friction coefficient of AISI 316 stainless steel samples decreased with increases in sliding velocity. Friction coefficient of AISI 316 stainless steel don't change with increasing the normal force. Coefficient of friction of Ti6Al4V alloys peened with A0.006 Almen intensity decreased in boundary friction operation conditions. On the other hand, friction coefficients of titanium samples peened with A0.008 and A0.010 Almen intensity increased. Depending on the increase of the sliding velocity, the coefficient of friction of Ti6Al4V alloy has been shown to variability in boundary friction operations conditions. Coefficients of friction of Ti6Al4V alloys peened with A0.006 Almen intensity and unpeened samples decreased with increases in sliding velocity. On the other hand, friction coefficients of titanium samples peened with A0.008 and A0.010 Almen intensity don't show important alteration. In addition, in boundary friction operation conditions, friction coefficients of Ti6Al4V alloy peened with A0.006 Almen intensity decrease in small value and friction coefficients of titanium samples peened with A0.008 and A0.010 Almen intensity increased in small ranges. In this study, wear rates of Ti6Al4V alloy and AISI 316 stainless steel samples have investigated in dry and boundary friction working conditions. In dry operation conditions, wear tests were conducted with 500 meters sliding distance, 10N normal force and 1 m/s sliding speed. In dry friction operation conditions, wear rates of Ti6Al4V alloy didn't change after shot peening implementation. In addition, AISI 316 stainless steel has exhibited increment in dry friction operation conditions. Wear rates of titanium alloy samples didn't change with increasing Almen intensity. However, wear rate values were exhibited reduction for stainless steel samples in dry friction operation conditions. In lubricated operation conditions, the amount of wear was measured depending on (500m, 1000m, 2000m, 3000m, 4000m and 5000m) the various sliding distance. Also wear tests were performed with 10N normal force and 1m/s sliding speed. After shot peening implementation, wear rates of titanium alloy and stainless steel decreased at lubricated operation conditions. In addition, wear rates of all samples decreased with the increase of Almen intensity. After sliding distance of 3000 meters, it has been observed that the wear rates of the sample became stable. As a result wear resistances of Ti6Al4V alloy were found to be higher than AISI 316 in dry and boundary friction operation conditions. Wear rates of titanium alloy and stainless steel samples were compared for 500 meters sliding distance, 10N normal force and 1 m/s sliding velocity. In boundary friction operation conditions, wear rates of Ti6Al4V alloy and AISI 316 stainless steel were observed low in comparison with in dry friction operation conditions. In addition, for all Almen intensities, the wear rate of Ti6Al4V alloy is observed the lowest in boundary friction conditions. As a result, the wear resistance of the material after shot peening applications developed for boundary friction conditions. Finally, the shot peened surface of the samples were examined by using stereo optical microscope and scanning electron microscope (SEM) in order to understand effect of shot peening implementation. With these methods, the effects of shot peening on the surface morphology of the samples have investigated. Plastic deformation has occurred on surface of materials due to shot peening media, which affect repeatedly and has very high impact velocity. Because of plastic deformations, pit and mound structures have been identified on sample surface with using optical microscopy. The surface morphology is specifically varied with shot peening implementation. The height of peaks and holes are increased sharply with increasing Almen intensity. Wear mechanisms have not changed with Almen intensity. But wear severity showed significant changes. According to results of study, the shot peening implementation and process parameters significantly affect the properties of the materials and dramatically play an active role in the tribological behaviors.
Experimental investigation of tribological behaviour of metallic materials after shot peening implementation
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Keywords: Titanyum alaşımları; Çelik; Paslanmaz; Sürtünme; Titanium alloys; Steel; Stainless; Friction